A Step in Between: [Sn3Bi3]5− and Its Structural Relationship to [Sn3Bi5]3− and [Sn4Bi4]4−. Issue 4 (25th May 2016) - Friedrich, Ute; Korber, Nikolaus
Abstract: Extraction of "RbSnBi" in liquid ammonia yielded the cluster anion [Sn3 Bi5 ] 3−, which could be crystallized in the compound [Rb@[2.2.2]crypt]3 [Sn3 Bi5 ]⋅8.87 NH3 . This anion is found to be derived from the formerly reported [Sn4 Bi4 ] 4− by the formal substitution of one tin atom by bismuth. In contrast, the extraction of "RbSn2 /Rb3 Bi2 " in liquid ammonia yielded the anion [Sn3 Bi3 ] 5− in the compound Rb6 [Sn3 Bi3 ][Sn4 ]1/4 ⋅6.75 NH3 . The structural correlation of the two novel clusters indicates that [Sn3 Bi3 ] 5− might be an intermediate of the reaction pathway to [Sn3 Bi5 ] 3− and [Sn4 Bi4 ] 4− . Each cluster is investigated by means of the electron localization function and further characterization was performed by using ESI‐MS. Abstract : Cage fight : The new crown‐like [Sn3 Bi3 ] 5− anion can be seen as the missing link between the also new [Sn3 Bi5 ] 3− anion and the previously reported [Sn4 Bi4 ] 4− anion. Both cages are formally derived by capping the crown with either a Bi−Bi or a Sn−Bi dumbbell. The main structural and electronic features of the fragment are conserved, especially the three‐center bond of the Sn triangle.